2019
DOI: 10.1002/jcp.29201
|View full text |Cite
|
Sign up to set email alerts
|

KIF18B promotes the proliferation of pancreatic ductal adenocarcinoma via activating the expression of CDCA8

Abstract: Pancreatic cancer is one of the malignant tumors with the worst prognosis, and the 5-year survival rate of this disease is less than 1%. About 90% of pancreatic cancer is pancreatic ductal adenocarcinoma (PDAC), and targeting therapy has become a promising treatment for PDAC in recent years. To improve the survival rate, novel therapeutic targets for PDAC are still urgently needed. KIF18B was initially identified as a member of the kinesin family and involved in multiple cellular processes, such as separation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 34 publications
2
34
0
Order By: Relevance
“…CDCA8 was also considered as an oncogene [22] in several types of cancers such as breast cancer [14], bladder cancer [23] and cutaneous melanoma [24]. The resent two studies and we all indicated that the mRNA level of CDCA8 was up-regulated in HCC and was associated with poor survival.…”
Section: Discussionmentioning
confidence: 66%
“…CDCA8 was also considered as an oncogene [22] in several types of cancers such as breast cancer [14], bladder cancer [23] and cutaneous melanoma [24]. The resent two studies and we all indicated that the mRNA level of CDCA8 was up-regulated in HCC and was associated with poor survival.…”
Section: Discussionmentioning
confidence: 66%
“…It has been reported that ~50% of patients have been confirmed to possess metastasized cancer cells (3). Despite continuous improvements in diagnosis and treatment, this type of cancer is almost invariably fatal, and the 5-year survival rate of patients is ~8% (4,5). PDAC has a high degree of malignant biological characteristics, including invasion and metastasis, which leads to a poor prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…KIF18B belongs to the kinesin 8 subfamily and is involved in the separation of chromosomes and spindle localization during mitosis [55]. In recent years, investigations have shown that KIF18B participates in the growth and development of a variety of cancers [11,56]. Per Li et al, KIF18B expression is regulated in a cell cycle-dependent manner and, therefore, could be involved in the regulation of cell cycle and cell proliferation [11].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, investigations have shown that KIF18B participates in the growth and development of a variety of cancers [11,56]. Per Li et al, KIF18B expression is regulated in a cell cycle-dependent manner and, therefore, could be involved in the regulation of cell cycle and cell proliferation [11]. Our analysis results revealed that KIF18B is an important regulator of HCC prognosis and is closely connected to cell cycle and DNA replication-related pathways, which provides ideas and strategies for our next focus on the role of KIF18B in HCC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation